Synthesis of New Chiral Crown Ethers Containing Phosphine or Secondary Phosphine Oxide Units - Szabó-Szentjóbi, Hajnalka; Majoros, István; Márton, Anna; Leveles, Ibolya; Vértessy, Beáta G.; Dékány, Miklós; Tóth, Tünde; Huszthy, Péter (Synthesis, 2020)
The transition-metal complexes of phosphine and secondary phosphine oxide compounds can be used in various catalytic reactions. In this paper, the synthesis and characterization of eight new crown ethers containing trivalent phosphorus in their macroring are reported. These macrocycles are promising candidates as ligands for catalytic reactions.
Keywords: crown ethers; macrocycles; phosphines; phosphine oxides; catalytic ligands